Does Strict Employment Protection Discourage Job Creation? Evidence from Croatia - Rutkowski, Jan (World Bank, Washington, DC, 2014)
Employment protection legislation in Croatia is among the most strict in Europe. Firing is difficult and costly, and flexible forms of employment are limited. Is this apparent rigidity reflected-as one would expect based on standard economic theory-in low labor market dynamics? Is job creation low and hiring limited? Is the job security of insiders achieved at the cost of outsiders not being able to enter the labor market? The author attempts to answer these questions by examining job flows. If the employment protection legislation is binding, then job and worker turnover should be low. He shows that this is indeed the case. Hiring is limited and the average job tenure is very long in Croatia. Job destruction is low, however job creation is still lower. The result is accumulation of unemployment, in large part due to new labor market entrants not being able to find a job. The high degree of job protection also seems to strengthen the bargaining position of insiders and results in relatively high wages. So, wages in Croatia are higher than among its competitors, even after adjusting for productivity. These high labor costs are likely to contribute to limited job creation in existing firms, but also are likely to discourage the entry of-and thus job creation in-new firms. The author presents evidence that firm growth has been indeed limited in Croatia, contributing to the low employment level. The author examines other potential causes of high unemployment in Croatia (the unemployment benefit system, labor taxation, the wage structure, and skill and spatial mismatches). He argues that they do not play a substantial part in accounting for poor labor market outcomes in Croatia. The author concludes that the stringent employment protection legislation is the key labor market institution behind low job creation and high unemployment. Based on this he recommends specific measures aimed at liberalizing the labor market to foster job creation and employment.